Biochemical Changes in the Liver After Covid-19 Disease in Alcohol-Dependent Patients and Their Effects on the Course of Alcoholism (The Peerian Journal, 2023)
In the vast majority of patients with alcoholism, various liver pathologies are observed. In patients receiving chronic alcohol products, at the expense of alcoholic intoxication, pathomorphological and fuctional changes in the liver are caused. This in turn leads to an increase in the tendency to various infectious diseases in the immune system and as a result at the expense of changes in the liver. In particular, the transmission of Covid-19 infection to my body is also facilitated. Even at the expense of Covid-19 infection, cytokines have a strong damaging effect on liver cells at the expense of storming and hypoxia. At the expense of these double effects, the changes in the liver do not have their own effect on the course of alcoholism.